Biomechanical investigation of the hybrid modified cortical bone screw–pedicle screw fixation technique: Finite-element analysis - Kahaer, Alafate; Maimaiti, Xieraili; Maitirouzi, Julaiti; Wang, Shuiquan; Shi, Wenjie; Abuduwaili, Nueraihemaiti; Zhou, Zhihao; Liu, Dongshan; Maimaiti, Abulikemu; Rexiti, Paerhati (Frontiers in Surgery, 2022)
Background: hybrid fixation techniques including the both modified cortical bone trajectory (MCBT) and traditional trajectory (TT) at the L4 and L5 lumbar segment are firstly proposed by our team. Therefore, the purpose of this study is to evaluate and provide specific biomechanical data of the hybrid fixation techniques, including the MCBT and TT. Methods: Four human cadaveric specimens were from the anatomy laboratory of Xinjiang Medical University. Four finite element (FE) models of the L4-L5 lumbar spine were generated. For each of them, four implanted models with the following fixations were established: TT-TT (TT screw at the cranial and caudal level), MCBT-MCBT (MCBT screw at the cranial and caudal level), hybrid MCBT-TT (MCBT screw at the cranial level and TT screw at the caudal level), and TT-MCBT (TT screw at the cranial level and MCBT screw at the caudal level). A 400-N compressive load with 7.5 N/m moments was applied to simulate flexion, extension, lateral bending, rotation, respectively. The range of motion (ROM) of the L4-L5 segment and the posterior fixation, the von Mises stress of the intervertebral disc and the posterior fixation were compared. Results: Compared to the TT-TT group, the MCBT-TT showed a significant lower ROM of the L4-L5 segment (P≤0.009), lower ROM of the posterior fixation (P＜0.001), lower intervertebral disc stress (P＜0.001), and lower posterior fixation stress(P≤0.041). TT-MCBT groups showed a significant lower ROM of the L4-L5 segment (P≤0.012), lower ROM of the posterior fixation (P＜0.001), lower intervertebral disc stress (P＜0.001), and lower posterior fixation stress(P≤0.038). Conclusions: The biomechanical properties of the hybrid MCBT-TT and TT-MCBT techniques at the L4-L5 segment are superior to that of stability MCBT-MCBT and TT-TT techniques, and feasibility needs further cadaveric study to verify.